2016
DOI: 10.1039/c5tc03504j
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric mechanosensitive fluorescent dyes: design and applications

Abstract: Fluorescent molecules, with their almost instantaneous response to external influences and relatively low-cost measurement instrumentation, have been attractive analytical tools and biosensors for centuries. More recently, advanced chemical synthesis and targeted design have accelerated the development of fluorescent probes. This article focuses on dyes with segmental mobility (known as fluorescent molecular rotors) that act as mechanosensors, which are known for their relationship of emission quantum yield wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 101 publications
0
71
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Viscosity-sensitive FMRs are attractive for use in variousa pplications including biomedical imaging and diagnosis by measuring the microviscosity of specific (sub-) cellular organelles and biomolecules. [5][6][7][8] In addition, FMRs are useful for detecting intra-channel viscosity in microfluidic devices and for measuring temperature-sensitive responses and specific phase transition temperatures (e.g.,g lass transition temperature). [1][2][3][4] FMRs are p-conjugated fluorescent molecules, termed as "fluorophores".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Viscosity-sensitive FMRs are attractive for use in variousa pplications including biomedical imaging and diagnosis by measuring the microviscosity of specific (sub-) cellular organelles and biomolecules. [5][6][7][8] In addition, FMRs are useful for detecting intra-channel viscosity in microfluidic devices and for measuring temperature-sensitive responses and specific phase transition temperatures (e.g.,g lass transition temperature). [1][2][3][4] FMRs are p-conjugated fluorescent molecules, termed as "fluorophores".…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2c,t he FL contrast( I/I 0 )g enerally follows the Fçrster-Hoffmann theory,l n(I/I 0 ) = C + xln(h), where Ci sa ne xperimental constant, x is the viscosity sensitivity of the FMR, and h is the viscosity of the medium. [6,7] The FL contrast strongly depends on the rotationa bility of rotators in the FMR. Pyrrolic rotators can rotate more easily than dimethylaminophenyl-based rotators, as shown in Figure 2a.C onsequently,a ss hown in Figure 2c,p yrrolic rotator-based FMRs exhibit an order of magnitude higherFLcontrast than those of dimethylaminophenyl rotator-based FMRs.…”
Section: Introductionmentioning
confidence: 99%
“…Additional proton transfer results in a Zwitterionic form that greatly destabilizes the excited state and undergoes rapid twisting to achieve high stability. Such intramolecular rotations occur typically around the σ‐bonds that connect the electronically rich donor and electronically poor acceptor units . The non‐linearity observed in the Lippert–Mataga plots also revealed intramolecular charge/energy transfer with increasing solvent viscosity.…”
Section: Resultsmentioning
confidence: 91%
“…Such intramolecular rotations occur typically around the σ-bonds that connect the electronically rich donor and electronically poor acceptor units. 25 The non-linearity observed in the Lippert-Mataga plots also revealed intramolecular charge/energy transfer with increasing solvent viscosity. The red-shifted emission confirmed that the donor-acceptor dyad system in 1 has a twisted Zwitterionic geometry in the excited state ( Figure S4(a) and (b)).…”
Section: Resultsmentioning
confidence: 95%
“…The viscosity is the experimental data from the reference, [35] which was also employed in Figure 3(a). According to the Förester-Hoffmann equation, [52,53] the ratio of MCR scores (I ratio ) and viscosity (η) are directly related through ð4Þ where A and x are constant depending on protein solution.…”
Section: Estimation Of the Microviscosity Using Mcr-resolved Ans Fluomentioning
confidence: 99%